A MUSCARONE-BINDING MATERIAL IN ELECTROPLAX AND ITS RELATION TO THE ACETYLCHOLINE RECEPTOR, I. CENTRIFUGAL ASSAY - O'Brien, R. D. (1969)
A muscarone-binding material has been found in Torpedo electroplax. The material behaves in several ways as one would expect of the binding component of the acetylcholine receptor, especially in its high affinity for muscarone (approximate K = 7 × 10(-6)M), acetylcholine (approximate K = 1.1 × 10(-6)M), curare, and nicotine, and its insensitivity to noncholinergic agents; the reversibility of its muscarone binding; and its suitably small amount (about 1.8 nmole/gm). The material appears not to be acetylcholinesterase.